Determinant factors of honey purchase and consumption in Trás-os-Montes region, Portugal - Ribeiro, Maria Isabel (2019)
Honey is considered the only food of animal origin that can be consumed without being processed. The honey is, also, considered a natural and healthy product with dietary, nutritional and medicinal characteristics. Quality, geographical region of production, information available on the products’ label, brand's reputation, variety, texture, taste, aroma, appearance, packaging and price are important factors when consumers choose to purchase honey. Thus, this research intends to identify determinant factors on which consumers base their purchasing decision. A cross-sectional study was developed based on a non-probabilistic sample of 474 individuals, of whom 399 were honey consumers. Data collection took place from March to May 2016 and was based on a questionnaire developed by Ribeiro et al. (2009), which was applied directly to consumers in the city of Bragança. Later, data was analysed with SPSS 23.0 software. The data analysis includes a univariate descriptive analysis and a multivariate analysis that involved the estimation of a binary logistic regression. The significant parameters of the logit model were taste, colour, origin and certification label, at a significance level of 1%. These characteristics explained 68.9% of the consumer's decision to purchase honey since consumers recognize authenticity and distinctive attributes of the product.